2022
DOI: 10.3390/jcm11071916
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei CNCM I 1572: A Promising Candidate for Management of Colonic Diverticular Disease

Abstract: Diverticular disease (DD) is a common gastrointestinal condition. Patients with DD experience a huge variety of chronic nonspecific symptoms, including abdominal pain, bloating, and altered bowel habits. They are also at risk of complications such as acute diverticulitis, abscess formation, hemorrhage, and perforation. Intestinal dysbiosis and chronic inflammation have recently been recognized as potential key factors contributing to disease progression. Probiotics, due to their ability to modify colonic micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…Diverticular disease (DD) is a common GI disorder. The alteration of intestinal microbiota and chronic inflammation are potential factors for disease progression [ 100 ]. Fecal material stasis leads to diverticular bacterial overgrowth, the impairment of the mucosal barrier function, inflammatory cytokine release, and low-grade inflammation.…”
Section: Microbiota and The Digestive Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Diverticular disease (DD) is a common GI disorder. The alteration of intestinal microbiota and chronic inflammation are potential factors for disease progression [ 100 ]. Fecal material stasis leads to diverticular bacterial overgrowth, the impairment of the mucosal barrier function, inflammatory cytokine release, and low-grade inflammation.…”
Section: Microbiota and The Digestive Pathologymentioning
confidence: 99%
“…Fecal material stasis leads to diverticular bacterial overgrowth, the impairment of the mucosal barrier function, inflammatory cytokine release, and low-grade inflammation. Microbiota disruption and mucosal inflammation are further associated with dysmotility and abdominal symptoms [ 100 ]. Genera including Enterobacter , Streptococcus and Bacteroides seem to be associated with DD, while lactobacilli and bifidobacteria reduce their level when used as a therapeutic option.…”
Section: Microbiota and The Digestive Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The three treatments were administered for 10 days each month over 12 months. This bacterial strain was chosen because it had previously been shown to colonize the human intestine, resist hydrochloric acid and bile salts, persist in the gastrointestinal tract for approximately two weeks after discontinuation of treatment, and be effective against gram-negative anaerobes [ 71 ]. L. casei was significantly better than placebo in maintaining SUDD remission, especially in combination with mesalazine.…”
Section: How Microbiota Changes Impact Dd Treatment: the Role Of Prob...mentioning
confidence: 99%
“…Lacticaseibacillus paracasei DG is a probiotic bacterium experimentally proven to survive gastrointestinal transit in adults 16 and children, 17 to modify the composition of the intestinal microbial ecosystem in healthy adults, 18 and to modulate immune responses in different intestinal conditions. 19 In addition, a multicenter, randomized, double-blind, crossover, placebo-controlled pilot trial (PROBE-IBS/1; ClinicalTrials.gov Identifier: NCT02371499) showed that strain DG (at least 24 billion CFU/capsule, two capsules per day) induced a significant reduction in Ruminococcus spp., a significant increase in fecal acetate and butyrate, and a significant reduction in the pro-inflammatory cytokine interleukin-15 when administered to IBS patients. 20 The results of the PROBE-IBS/1 trial suggested that the clinical efficacy of L. paracasei DG could be greater in patients with IBS-D and IBS-M and encouraged the conduct of a larger study (named PROBE-IBS/2) to assess the effect of Enterolactis Ⓡ PLUS capsules (a single-strain probiotic formulation containing at least 24 billion CFUs of L. paracasei DG) on abdominal symptoms in non-constipated IBS (NC-IBS) patients without constipation.…”
Section: Introductionmentioning
confidence: 99%